Awareness about Workplace Harassment among Female Nursing Students and Nursing Staff of a Teaching Hospital in Lahore - Tahseen Kazmi; Jamal Abdul Nasir; Umaila Qayyum; Tehreem Tahir (Shalamar Medical & Dental College, Lahore, Pakistan, 2021)
Background: Harassment of working women is a common social and human rights problem and healthcare settings are no exception. This unacceptable situation has many avoidable determinants that need preventive measures to ensure, safe and secure working environment for nurses. Objectives: To assess the knowledge and understanding among female nursing students and nursing staff about workplace harassment in a tertiary healthcare facility. Methods: It was a cross-sectional study conducted at Tertiary care hospital Lahore from July to September 2018. Convenient sampling technique was used to collect data. Verbal informed consent of voluntary participants was taken. Anonymity and confidentiality was assured. SPSS version 21 was used for data analysis. The participants (n=80) comprised of senior female nurses students (62.5%) and senior nursing staff (37.5%), aged 18 to 46 years. Results: Awareness about common harassment forms was adequate (81.3%). Adverse effects included mental health problems (83.8%) and low self-esteem (72.5%). A large percentage of nurses (62.5%) intended to report such personal incident to institutional head and 72.5% were willing to accompany victims for such reporting. 77.5% desired arranging informative sessions and holding counseling for victims (78.8%) at workplace. Only 22.5% had vague idea about official protective legal frameworks. Conclusions: Workplace harassment of female workers is quite prevalent but under-reported phenomena in Pakistan. All organizations and institutions must have a harassment policy to protect the females.